Successful Conservative Treatment of an Elderly Patient with Corrosive Proctocolitis - Chalerm Eurboonyanun; Somchai Ruangwannasak; Kulyada Eurboonyanun; Anan Sripanuskul (Case Reports in Surgery)
Corrosive proctocolitis has occurred after accidental contamination of endoscopes in most patients. But accidental administration of corrosive agents for bowel cleansing can occur. The agents implicated for chemical colitis is 15% hydrochloric acid and 2% ethoxylated alcohol. We present a case of corrosive proctocolitis, present with anal pain and bloody diarrhea. Endoscopy revealed edema, erythema, and friability of the colonic mucosa. An experience of successful nonoperative treatments has been demonstrated.